2018
DOI: 10.1016/j.ymthe.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Limitations Inherent in Sulfamidase to Improve Mucopolysaccharidosis IIIA Gene Therapy

Abstract: Sulfamidase (SGSH) deficiency causes mucopolysaccharidosis type IIIA (MPS IIIA), a lysosomal storage disease (LSD) that affects the CNS. In earlier work in LSD mice and dog models, we exploited the utility of adeno-associated viruses (AAVs) to transduce brain ventricular lining cells (ependyma) for secretion of lysosomal hydrolases into the cerebrospinal fluid (CSF), with subsequent distribution of enzyme throughout the brain resulting in improved cognition and extending lifespan. A critical feature of this ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…Thus, the intrinsic biochemical properties has to be closely considered when to assess the applicability of the chemical modification approach for other lysosomal enzymes. The recombinant Sulfamidase produced in this study was remarkably stable, and both rhSulfamidase and CM-rhSulfamidase appeared to be retained within the cells, which agrees with studies of sulfamidase being poorly secreted from transduced cells [8,25]. The strong intracellular retention and stability may be key features enabling effective intra-lysosomal concentrations of CM-rhSulfamidase in CNS after repeated administration.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the intrinsic biochemical properties has to be closely considered when to assess the applicability of the chemical modification approach for other lysosomal enzymes. The recombinant Sulfamidase produced in this study was remarkably stable, and both rhSulfamidase and CM-rhSulfamidase appeared to be retained within the cells, which agrees with studies of sulfamidase being poorly secreted from transduced cells [8,25]. The strong intracellular retention and stability may be key features enabling effective intra-lysosomal concentrations of CM-rhSulfamidase in CNS after repeated administration.…”
Section: Discussionsupporting
confidence: 86%
“…To test whether this is an effect of overexpression of transgenes in animals null for a disease gene, we subsequently examined brain sections from mucopolysaccharidosis type IIIA (MPS IIIA) sulfamidase (SGSH) homozygous knockout mice treated with AAV4 expressing human SGSH, a secreted protein, using the same dose, injection coordinates, and volume as in our AAV4.GRN studies. 51 There was no observed toxicity in treated MPS IIIA mice (data not shown), supporting an effect specific to GRN.…”
Section: A T Cell-mediated Inflammatory Response Precedes Neuronal Lomentioning
confidence: 67%
“…with AAV4.SGSH, a secreted protein, using the same approach as our study, showed no sign of hippocampal or ventricular degeneration or of cellular infiltrate. 51 Cumulatively, the data suggest that our results are specific to overexpression of GRN as a target gene, rather than route of delivery, dose, expression of a human gene in a null mouse model, or expression of a secreted protein.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations